PENANGANAN DISPOSAL AREA DI PT. HASABA GLOBAL MATERINDO, KECAMATAN PANGKALAN, KABUPATEN LIMA PULUH KOTA, PROVINSI SUMATERA BARAT. - septian anugrah; Rudy Anarta (Journals Mining Engineering : Bina Tambang, 2023)
PT. Hasaba Global Materindo (HGM) according to production mining business permit 544 -188- 2019 has a mining land concession of 17.7 hectares located in Polong Duo, Nagari Koto, Pangkalan Koto Baru District, Lima Puluh Kota District. Because there is a disposal area that is no longer used at PT. Hasaba Global Materindo, which causes dust in dry season and puddles in rainy season, requires an activity as an effort to preserve the environment so that further damage does not occur. And one way that can be done is to handle the disposal area. Handling the disposal area must also meet success in order to achieve maximum results. The unused landfill area has an area of 1.09 Ha which will be handled later. Handling of the disposal area starts with spreading top soil as a planting medium, spreading top soil with a thickness of 150 cm, with a required soil volume of 15,135.67m³ using 1 cat D-6R bulldozer, 1 paint excavator PC 320D, and 5 FUSO 220 PS dump trucks. After the land arrangement complete, the land will be carried out to hide the cover crop. Cover crop planting for an area of 10090.45 m² or 1.009045 Ha, will use Pueraria javanica seeds, totaling 4.36 Kg. Furthermore, the revegetation process which consists of procuring seeds with the number of oil palm seeds requiring 154 stems. At the planting stage, the spacing of the oil palms is 8.5 m x 8.5 m with the dimensions of the planting hole being 60 cm x 60 cm. As well as maintenance for 1 year after the seeds are planted which consists of weeding, fertilizing, and embroidery. Based on calculations in handling area disposal by revegetation, the total cost of handling area disposal is Rp. 222,927,900